Financial Literacy, Financial Experience, and Financial Attitudes on Financial Management Behavior of Shopee Paylater Users - Safitri, Isna; Hariyanto, Dedi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study explores the factors influencing financial management behavior among Shopee PayLater users, focusing on financial literacy, financial experience, and financial attitudes. The research was conducted in Pontianak City, targeting individuals who actively use Shopee PayLater services. By employing a purposive sampling technique, the study identifies the relative contributions of these factors to financial management behavior. The findings highlight the importance of financial attitudes as a key determinant, while financial literacy and financial experience show a less significant direct influence. These insights underscore the need for tailored interventions that prioritize shaping positive financial attitudes to improve financial behavior among digital credit users.